2020
DOI: 10.1080/07391102.2020.1780947
|View full text |Cite
|
Sign up to set email alerts
|

Natural compounds fromClerodendrumspp. as possible therapeutic candidates against SARS-CoV-2: Anin silicoinvestigation

Abstract: The COVID-19 pandemic caused by the novel coronavirus SARS-CoV-2 has rattled global public health, with researchers struggling to find specific therapeutic solutions. In this context, the present study employed an in silico approach to assess the inhibitory potential of the phytochemicals obtained from GC-MS analysis of twelve Clerodendrum species against the imperative spike protein, main protease enzyme M pro and RNA-dependent RNA polymerase (RdRp) of SARS-CoV-2. An extensive molecular docking investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 97 publications
0
71
0
Order By: Relevance
“…The compounds anisotine (1.90 lM), adhatodine (7.35 lM), beta-carotene (5.24 lM), eugenol (4.42 lM), mangiferin (3.16 lM) and beta-amyrin (6.21 lM) were predicted to be potent inhibitors and promising lead compounds based on our observations of inhibition constant values (Table 1). Recently, our group (Kar et al, 2020) conducted an interaction profiling of the drug arbidol, that is commonly targeted against SARS-CoV-2 spike protein to inhibit viral attachment with human ACE2 receptor, and reported a binding energy score of À6.2 kcal/mol with the RBD of SARS-CoV-2 spike protein (Kar et al, 2020;Sanders et al, 2020). It was interesting to note that the compounds anisotine, adhatodine, beta-carotene, eugenol, mangiferin and beta-amyrin exhibited significantly higher binding energy scores (p < 0.01) (Table 1) with respect to the drug arbidol.…”
Section: Molecular Docking Of the Phytocompounds With The Receptor-bimentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds anisotine (1.90 lM), adhatodine (7.35 lM), beta-carotene (5.24 lM), eugenol (4.42 lM), mangiferin (3.16 lM) and beta-amyrin (6.21 lM) were predicted to be potent inhibitors and promising lead compounds based on our observations of inhibition constant values (Table 1). Recently, our group (Kar et al, 2020) conducted an interaction profiling of the drug arbidol, that is commonly targeted against SARS-CoV-2 spike protein to inhibit viral attachment with human ACE2 receptor, and reported a binding energy score of À6.2 kcal/mol with the RBD of SARS-CoV-2 spike protein (Kar et al, 2020;Sanders et al, 2020). It was interesting to note that the compounds anisotine, adhatodine, beta-carotene, eugenol, mangiferin and beta-amyrin exhibited significantly higher binding energy scores (p < 0.01) (Table 1) with respect to the drug arbidol.…”
Section: Molecular Docking Of the Phytocompounds With The Receptor-bimentioning
confidence: 99%
“…Biological diversity has afforded mankind an invaluable source of molecular entities that have, for centuries, been a resource in the production of traditional and formal pharmaceuticals (Kar et al, 2020 ). The process of drug discovery relies heavily upon phytochemicals as remedies to various ailments.…”
Section: Introductionmentioning
confidence: 99%
“…Enisamium was shown to inhibit the activity of the SARS-CoV-2 RNA polymerase and its active metabolite exhibits similar efficacy with remdesivir triphosphate, it is approved in 11 countries and does not require intravenous administration, unlike remdesivir ( Walker et al, 2020 ). In silico approaches have also been used to identify novel inhibitors, either by screening clinically used polymerase inhibitors, or FDA approved drugs and/or natural compounds ( Kar et al, 2020 ; Pokhrel et al, 2020 ; Ruan et al, 2020 ; Zhang et al, 2020b ).…”
Section: Non-structural Proteins As Potential Drug Targetsmentioning
confidence: 99%
“…Chen et al screened Thioflexibilolide A (Binding Energy: −9.2 kcal/mol) and Candidine (Binding Energy: −9.0 kcal/mol) as best compounds from 2000 natural compounds (Chen et al, 2020). Kar et al performed docking study with natural compounds from Clerodendrum spp., and reported that Taraxerol ( G bind prime MM-GBSA = −45.19 kcal/mol) as most promising inhibitory candidate against the SARS-CoV-2 spike protein (Kar et al, 2020). All the above reported compounds have shown to interact with amino acids in the ACE2-RBD interface region.…”
Section: Affinity and Stability Of Selected Natural Productsmentioning
confidence: 99%